Mobile Phone Data and Urban Analysis: An Exploratory Space – Time Study - Emmanouil Tranos; John Steenbruggen; Peter Nijkamp (Tinbergen Institute, 2013)
This paper discusses the value that data from mobile phone providers can bring into urban analysis. The novel argument is that the pervasiveness of mobile phone telephony has transformed mobile phones from a communications device to a tool for socio-spatial research. Put simply, mobile phone providers can potentially gather relevant data on a very refined spatio-temporal scale for every 85 out of 100 inhabitants in the world. Such data can include basic information about personal communication patterns, interactions and mobility which can enable researchers to better understand spatial human behavior, the predictability of which is well documented. These advances that have mostly taken place in the complexity science domain, which largely focuses on individual behavioural patterns, can also result in applications in the spatial analysis domain. This paper has two aims. Firstly, we critically discuss the existing state of the art of urban analysis based on big data from mobile phone operators. Based on this review, the paper takes a methodological turn to present some preliminary urban analysis results using data from a mobile phone operator in Amsterdam, The Netherlands.
Keywords: O1; L63; 330; Economics; Stadtentwicklung; Mobilkommunikation; Datenqualität; Amsterdam